2013
DOI: 10.3109/15563650.2013.791695
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of serum ethanol concentration to the osmol gap: a prospective volunteer study

Abstract: In this volunteer study, the coefficient describing the contribution of ethanol to serum osmolality (k) was found to be 4.25. This indicates that ethanol contributes more to total serum osmolality than would be predicted for an ideal solute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…When examining the mean difference, there was no significant difference between Formula 5a and measured ethanol, but there were constant and proportional differences between the measurement and the Formula 5a result. Our results indicating that the coefficient for ethanol should be greater than 1/4.6 agreed with the findings of several studies [9][10][11]. But it may vary with increasing ethanol concentrations, as ethanol may affect the solubility of solutes in serum as a solvent.…”
Section: Discussionsupporting
confidence: 81%
“…When examining the mean difference, there was no significant difference between Formula 5a and measured ethanol, but there were constant and proportional differences between the measurement and the Formula 5a result. Our results indicating that the coefficient for ethanol should be greater than 1/4.6 agreed with the findings of several studies [9][10][11]. But it may vary with increasing ethanol concentrations, as ethanol may affect the solubility of solutes in serum as a solvent.…”
Section: Discussionsupporting
confidence: 81%
“…The osmol gap was divided by the blood ethanol to determine the mean coefficient of ethanol's contribution to serum osmolality, yielding 4.25 (95 % CI,. This divisor is smaller than that predicted by molecular weight of ethanol, indicating that it contributes more to total osmolality than predicted for an ideal solute [191]. The study has been criticized for proposing a mean coefficient when the underlying individual subjects had coefficients that were substantially inconsistent [193].…”
Section: Mass Unitsmentioning
confidence: 82%
“…Two more recent studies have studied the effect of ethanol on the osmol gap [191,192]. Carstairs and colleagues gave ten healthy volunteers up to 140 mL 100 % ethanol in sugar-free soda (n = 8) or plain sugar-free soda (n = 2).…”
Section: Mass Unitsmentioning
confidence: 99%
“…The differing results reported by various investigators may be related to the varying characteristics of study samples (e.g., presence and absence of ethanol intake, or healthy volunteers) or data manipulation (compared with ethanol and osmolality which diminished ethanol contribution) 6,13,14) . The present study was conducted to validate the formula derived by Purssell et al 5,15) that linked ethanol concentration with OG.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the correlation between the calculated ethanol level using OG and the measured ethanol level in patients with suspected acute poisoning was 0.704 (range in subgroups, 0.412-0.835). In previous studies, Pearson correlation coefficients were ranged from 0.93 to 0.994 for healthy volunteers or patients poisoned with known toxic alcohols 1,4,5, 13,14,17) . Chang et al 19) reported that the correlation between OG and measured ethanol level was 0.916 in all non-trauma and trauma patients; 0.939 non-trauma without shock patients; 0.917 in trauma without shock patients; and 0.844 trauma patients with shock.…”
Section: A B C Dmentioning
confidence: 99%